1993
DOI: 10.1523/jneurosci.13-09-04015.1993
|View full text |Cite
|
Sign up to set email alerts
|

Directionally selective mnemonic properties of neurons in the lateral dorsal nucleus of the thalamus of rats

Abstract: The hippocampal formation has been extensively studied for its special role in visual spatial learning and navigation. To ascertain the nature of the associations made, or computations performed, by hippocampus, it is important to delineate the functional contributions of its afferents. Therefore, single units were recorded in the lateral dorsal nucleus of the thalamus (LDN) as rats performed multiple trials on a radial maze. Many LDN neurons selectively discharged when an animal's head was aligned along parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
246
3
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(267 citation statements)
references
References 53 publications
17
246
3
1
Order By: Relevance
“…When a rat reenters a familiar test environment, it has to be exposed to its visual surroundings in order to reset its head direction system. If the lights are then turned off, the cells maintain their direction specific firing for a given time span; their activity then starts drifting, as expected, if we assume that the updating process occurred through the angular components of self-motion cues (Mizumori and Williams, 1993). Likewise, in a cylindrical test apparatus with a single cue card, the head direction cells may maintain their directional preference after the removal of the cue card, but this preference drifts slowly over time.…”
mentioning
confidence: 52%
“…When a rat reenters a familiar test environment, it has to be exposed to its visual surroundings in order to reset its head direction system. If the lights are then turned off, the cells maintain their direction specific firing for a given time span; their activity then starts drifting, as expected, if we assume that the updating process occurred through the angular components of self-motion cues (Mizumori and Williams, 1993). Likewise, in a cylindrical test apparatus with a single cue card, the head direction cells may maintain their directional preference after the removal of the cue card, but this preference drifts slowly over time.…”
mentioning
confidence: 52%
“…Upon the entry to a familiar environment, head direction ⌽ is initialized with value ⌽ vis by setting ␣ hd ϭ 1. While our model of the head direction network (see Equations A8 and A11) is algorithmic (Franz, Schölkopf, Mallot, & Bülthoff, 1998), rather than neuronal, it captures the fact that head direction cells are anchored to visual cues of the environment (Mizumori & Williams, 1993).…”
Section: Snapshot-based Estimation Of Head Directionmentioning
confidence: 99%
“…HD cells were first electrophysiologically recorded in the rat postsubiculum (PoSC) (Ranck, 1984;Taube et al, 1990a), and then found in numerous other structures including the laterodorsal thalamic nucleus (Mizumori and Williams, 1993), the dorsal striatum (Wiener, 1993), the retrosplenial cortex (Chen et al, 1994), the anterodorsal thalamic nucleus (ADN) (Taube, 1995;Blair and Sharp, 1995), the lateral mammillary nucleus (LMN) (Stackman and Taube, 1998), and the dorsal tegmental nucleus (DTN) .…”
Section: Introductionmentioning
confidence: 99%